On the Dynamics and Water Mass Transformation of a Boundary Current Connecting Alpha and Beta Oceans - Lambert, Erwin; Eldevik, Tor; Spall, Michael A. (Journal of Physical Oceanography, 2018)
A subpolar marginal sea, like the Nordic seas, is a transition zone between the temperature-stratified subtropics (the alpha ocean) and the salinity-stratified polar regions (the beta ocean). An inflow of Atlantic Water circulates these seas as a boundary current that is cooled and freshened downstream, eventually to outflow as Deep and PolarWater. Stratification in the boundary region is dominated by a thermocline over the continental slope and a halocline over the continental shelves, separating Atlantic Water from Deep and Polar Water, respectively. A conceptual model is introduced for the circulation and water mass transformation in a subpolar marginal sea to explore the potential interaction between the alpha and beta oceans. Freshwater input into the shelf regions has a slight strengthening effect on the Atlantic inflow, but more prominently impacts the water mass composition of the outflow. This impact of freshwater, characterized by enhancing Polar Water outflow and suppressing Deep Water outflow, is strongly determined by the source location of freshwater. Concretely, perturbations in upstream freshwater sources, like the Baltic freshwater outflow into the Nordic seas, have an order of magnitude larger potential to impact water mass transports than perturbations in downstream sources like the Arctic freshwater outflow. These boundary current dynamics are directly related to the qualitative stratification in transition zones and illustrate the interaction between the alpha and beta oceans. Copyright 2018 AMS publishedVersion